Polymeric particulate system of carboxymethyl chitosan-diterpen lactone fraction of Andrographis paniculatas Nees: Characterization and in vitro release study - Retno Sari (Sphinx Knowledge House, 2016)
Abstract: Objective: The objective of this research was to enhance the dissolution characteristic of diterpene lactone fraction of Andrographis paniculata Nees (DTLF) containing 75.9% andrographolide. The effect of carboxymethyl chitosan concentration on physical characteristics, entrapment efficiency and in vitro release of diterpene lactone fraction of Andrographis paniculata Nees (DTLF) particulate system were investigated. Methods : Diterpene lactone fraction of Andrographis paniculata Nees (DTLF) particulate system with different amount of carboxymethyl chitosan (CMChi) were prepared by ionic gelation followed by spray drying methods with CaCl2 as cross linker. The particles were evaluated in terms of physical state, drug entrapment efficiency and in vitro release rate. Results : The result showed that DTLF is already entrapped in the system hence the crystallinity reduced. The entrapment efficiency increases with increasing the amount of carboxymethyl chitosan, between 84% up to 90%. The release rate of the particles in 0.5% SLS media were 1.5 times higher than DTL substance, but not significantly different as the polymer amount increased. Conclusion : Entrapment of DTL in CMChi particulates system could reduce the crystallinity. Hence DTL – CMChi particles were able to enhance release rate of DTL up to 1.5 times.